Partnering for impact: best practices for planning in-person academic events with Patient Partners involvement– Lessons learned from Diabetes Action Canada - Tracy McQuire; Jamie Boisvenue; Katharine Mackett; Jasmine Maghera; Julie Makarski; Al Martin; Linxi Mytkolli; Mildred Lim; Conrad Pow; Holly O. Witteman (Research Involvement and Engagement)
Abstract Health-related academic events that focus on patient-oriented research should prioritize the needs and interests of those most affected by their outcomes. Diabetes Action Canada (DAC) has hosted six in-person workshops over eight years, bringing together over 100 participants from research, healthcare delivery, government, non-profit organizations, and communities with lived experience of diabetes. This paper outlines key lessons and best practices from Diabetes Action Canada’s collaborative approach to workshop co-design with Patient Partners. For the 2024 workshop, a planning committee, largely composed of Patient Partners, played a central role in shaping the agenda. Their contributions ensured active patient participation, addressed power imbalances, fostered inclusivity, and created supportive spaces. Strategies such as co-designed agendas, symbolic markers for patient-led presentations, and facilitated networking sessions effectively enhanced engagement. Evaluations highlighted the importance of equitable participation and multidisciplinary collaboration, emphasizing the scalability of DAC’s co-design principles for diverse research and healthcare contexts. These insights provide a foundation for inclusive, impactful, and patient-centered event planning.